Peningkatan Kapasitas Masyarakat untuk Mitigasi Bencana dan Pelestarian Lingkungan melalui Edukasi dan Aksi Penanaman di Kota Ambon - Irwanto Irwanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Indonesia is highly susceptible to natural disasters owing to its geographical location at the intersection of three major tectonic plates. Effective disaster mitigation requires active community participation through education and tangible environmental conservation measures. This community engagement initiative aimed to strengthen community capacity for disaster mitigation and environmental preservation through cross-sectoral collaboration involving the Regional Disaster Management Agency (BPBD), the Faculty of Agriculture at Pattimura University, and the Sagu Salempeng GPM Foundation. Implementation methods comprised disaster mitigation education, extension services on conservation plant cultivation, memorandum of understanding (MoU) signing, and seedling distribution to 12 representatives from 6 villages in Ambon City, Maluku region. Outcomes revealed enhanced community comprehension of disaster mitigation concepts and strengthened commitment toward planting productive species for environmental conservation purposes. This initiative contributes to community resilience development and reinforces Indonesia's Disaster Resilient Village program.